Two-Phase Flow Process and Atomization Law of Nucleator Nozzle for an Outdoor Snow Maker - Hao Yahui; Wu Haifeng; Xu Rongji; Zhang Hua; Wang Ruixiang (Zhileng xuebao, 2025)
Nucleator nozzles play an important role in promoting the rapid nucleation, crystallization, and snow formation of artificial snow droplets. A visual experimental platform was designed to investigate the gas-liquid two-phase flow process inside the nucleator nozzle and its influence on atomization behavior. The results showed the presence of a two-phase annular flow within the nucleator nozzle and a continuous hollow-cone spray field outside the nucleator nozzle. As the gas-liquid pressure ratio (ΦGL) increases, the interfacial disturbance waves at the gas-liquid interface of the internal flow gradually disappear. As the air core occupied more space, the liquid film thickness gradually decreased and became uniform and stable. This markedly improved the atomization efficiency and quality. When the ΦGL was increased from 20% to 67%, the uniformity and stability of droplet distribution increased by 17% and 60%, respectively. This research offers important guidance for the structural design of high-performance atomized components.